Аpplication of the capillary electrophoresis method in the analysis of water-soluble vitamins of representatives of the genus Rubus L. - M. B. Ilina; E. V. Sergunova (Разработка и регистрация лекарственных средств, 2025)
Introduction. Capillary electrophoresis is a method of separating a mixture of substances in a high voltage field. The method is used to analyze compounds of organic and inorganic nature and has a number of advantages: cheapness, safety, simplicity of equipment. The method is also gaining popularity in the analysis of the chemical composition of plant raw materials.Aim. The study of the vitamin composition in plant raw materials of representatives of the genus Rubus L. by capillary electrophoresis.Materials and methods. The objects of the study were the dried leaves and/or fruits of plants such as Rubus caesius L. (European dewberry), Rubus nessensis Hall (European blackberry), Rubus allegheniensis Porter (allegany blackberry), Rubus ulmifolius Scott (elmleaf blackberry), Rubus saxatilis L. (roebuck berry), Rubus idaeus L. (raspberry), Rubus chamaemorus L. (cloudberry), Rubus arcticus L. (arctic raspberry). Detection and quantitative determination of water-soluble vitamins was carried out in the capillary electrophoresis system Kapel-104T (Group of Companies "Lumex", Russia). The analysis was carried out in a variant of capillary electrophoresis – micellar electrokinetic chromatography.Results and discussion. Under the specified analysis conditions, 5 B vitamins (nicotinamide, riboflavin, pyridoxine, nicotinic acid, thiamine) and vitamin C (ascorbic acid) were identified. The vitamin content in different types of raw materials varied. It is noted that riboflavin, ascorbic and nicotinic acids are present in almost all the studied objects. In terms of quantitative content, the predominant vitamins in the leaves are nicotinamide, ascorbic acid and pyridoxine, in fruits – ascorbic acid and thiamine. The total vitamin content in the leaves is higher than in the fruits, which is explained by different drying conditions.Conclusion. By the method of capillary electrophoresis, it was possible to detect and quantify water-soluble vitamins in plant raw materials using the example of some representatives of the genus Rubus L. In general, the vitamin content in the studied raw materials is low, some of them are marked by the largest number of these compounds – R. caesius L. and R. saxatilis L.